AUGUSTINUS: POTRET SEJARAWAN MASA PERTENGAHAN DAN KONTRIBUSI BAGI KAJIAN SEJARAH ISLAM - Herawati Herawati (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2012)
The main characteristic of medieval period is Theosentris, churchdomination and feudalistic. In this period, the whole order of society governedentirely by the religion (dogma) or the church. Therefore, reason and rationalityis pressed even silenced so as not contrary to the church. This condition is thenled to the declining of Europe, or better known as the